Stereoselective Total Synthesis of Pinolide and Its C2 Epimer and Evaluation of Their Cytotoxic Activity - Jangili, Paramesh; Kumar, C. Ganesh; Poornachandra, Y.; Das, Biswanath (Synthesis, 2015)
Pinolide, a naturally occurring nonenolide and its C2 epimer have been synthesized using d-mannitol and 1,2-epoxyhex-5-ene as the starting materials. The synthesis involves the Jacobsen’s hydrolytic kinetic resolution, Yamaguchi esterification, and intramolecular ring-closing metathesis as the key steps. The 2-epi-pinolide, the C2 epimer of pinolide, has been synthesized for the first time. The cytotoxic activity of the pinolide and 2-epi-pinolide has been studied.
Keywords: pinolide; total synthesis; d-mannitol; 1,2-epoxyhex-5-ene